Building Modern Transformation through Fazlur Rahman’s Double Movement Method in Interpreting the Qur’an - Maulana, Alif; Azizah, Hanifatul; Turmudi, Ahmad; Anam, Syahru Ramadhanil; Rinaldi, Muhammad Syafiq; Rosa, Andi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
In the contemporary era, Muslim engagement with the Qur’an and Hadith faces increasingly complex and multidimensional challenges, including issues of gender, globalization, scientific advancement, and social transformation. Previous studies on Fazlur Rahman’s hermeneutical approach have largely been descriptive, while relatively few have examined the double movement method as a framework for a transformative and contextually relevant interpretation of the Qur’an. This study aims to analyze how Rahman’s double movement functions as a mechanism that bridges the historical-contextual origins of revelation with contemporary ethical and social realities. This research employs a qualitative design based on a library research approach. The primary data sources of this study consist of scholarly literature examining Fazlur Rahman’s thought, particularly his double movement hermeneutical approach and contemporary Qur’anic interpretation. The secondary data sources include studies on modern tafsir and relevant discourses in contemporary Islamic thought. Data were collected through systematic literature review and in-depth textual analysis, and analyzed using a descriptive-analytical method to critically examine the conceptual and methodological framework of Rahman’s thought. The findings indicate that the double movement operates through two dialectical stages: first, situating Qur’anic texts within their historical context to extract universal moral principles; and second, recontextualizing theseprinciples within contemporary social settings. Its application to Q.S. al-Mujādalah :11 demonstrates the method’s capacity to transform historically specific directives into ethically relevant guidance that promotes social inclusivity, respect for knowledge, and justice. The study concludes that Rahman’s double movement offers a robust hermeneutical framework for an ethical, contextual, and socially relevant interpretation of the Qur’an.